2016
DOI: 10.1063/1.4961685
|View full text |Cite
|
Sign up to set email alerts
|

Invited Article: Electrically tunable silicon-based on-chip microdisk resonator for integrated microwave photonic applications

Abstract: Silicon photonics with advantages of small footprint, compatibility with the mature CMOS fabrication technology, and its potential for seamless integration with electronics is making a significant difference in realizing on-chip integration of photonic systems. A microdisk resonator (MDR) with a strong capacity in trapping and storing photons is a versatile element in photonic integrated circuits. Thanks to the large index contrast, a silicon-based MDR with an ultra-compact footprint has a great potential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Continuous delay settings can also be obtained using bulk optical assemblies that build on a tunable path delay through internal reflection mechanisms [11,17] or spatial light modulators that enable arbitrary phase shifts [16]. Alternatively, highly compact elements that offer a tunable group delay at resonance, such as micro resonators [31][32][33][34][35][36][37] or waveguide gratings [38][39][40] can be directly implemented in InP, SiN or silicon-on-insulator based integrated circuits. A combination of switched binary delays and a smaller continuous delay element enables larger delays of up to 1.8 ns [32].…”
Section: State-of-the-art In True-time Delays and Photonic-assisted Rf Beamformersmentioning
confidence: 99%
“…Continuous delay settings can also be obtained using bulk optical assemblies that build on a tunable path delay through internal reflection mechanisms [11,17] or spatial light modulators that enable arbitrary phase shifts [16]. Alternatively, highly compact elements that offer a tunable group delay at resonance, such as micro resonators [31][32][33][34][35][36][37] or waveguide gratings [38][39][40] can be directly implemented in InP, SiN or silicon-on-insulator based integrated circuits. A combination of switched binary delays and a smaller continuous delay element enables larger delays of up to 1.8 ns [32].…”
Section: State-of-the-art In True-time Delays and Photonic-assisted Rf Beamformersmentioning
confidence: 99%
“…TTDLs provide a unique solution for broadband signal processing, such as tunable high-resolution microwave filters [89,90], beam forming in phased array antennas [91,92] etc. We review here three different implementations reported in the literature recently: a PN junction loaded microdisk cavity offering electrical tunability of group delay although suffering from lower bandwidth [93], an interesting demonstration involving subwavelength grating (SWG) waveguide which does not suffer from bandwidth limitations [94], and finally, a continuously tunable delay line using a cascade of switches and dual rings [95]. Moreover, we also review a 1 × 4 beam steering system for phased array antennas (PAA) using 1-D grating waveguides based TTDLs [96].…”
Section: True Time Delay Line and Beam Steeringmentioning
confidence: 99%
“…A microdisk resonator (MDR) based electrically tunable delay line in SOI was demonstrated in [93], as depicted in Figure 8a. A MDR exhibits better performance in terms of footprint and light confinement factors compared to conventional micro ring resonators.…”
Section: True Time Delay Line and Beam Steeringmentioning
confidence: 99%
See 1 more Smart Citation
“…16 For semiconductor devices, additionally an injection of free-carriers can be applied to alter the refractive index. 15,23,24 While tuning based on the electro-optical effect and free-carrier dispersion effect can be realized at high speed, the tuning range is rather small. Conversely, thermal tuning operates with low or moderate speed, but typically possesses larger tuning ranges.…”
Section: Introductionmentioning
confidence: 99%